Peningkatan Keterampilan Kolaborasi Peserta Didik Melalui Penerapan Model Problem Based Learning Dengan Pendekatan Teaching at The Right Level (TaRL): Improving Students' Collaboration Skills Through the Application of the Problem Based Learning Model with the Teaching at the Right Level (TaRL) Approach - Sri Indriani, Sri Indriani; Ja’faruddin, Ja’faruddin; Ahmad, Habriah (Jurusan Pendidikan Teknik Elektro, 2025)
This research is a Classroom Action Research (CAR) which is carried out in two cycles,Each cycle consists of four stages, namely planning, implementation, observation, and reflection. This researchaims toimproving students' collaboration skills through the application of the problem based learning (PBL) model with the Teaching at The Right Level (TaRL) approach to students in class X.1 of SMA Negeri 11 Makassar with 35 students as subjects.The data collection technique used was observation. The results of the study showed that the implementation of learning using the problem based learning (PBL) model with the Teaching at The Right Level (TaRL) approach can improve students' collaboration skills. This is evidenced by an increase in the average percentage of students' collaboration skills from 56% in the pre-cycle to 65% in cycle 1, then increasing again to 80% in cycle 2.